An Analysis of Lebih Senyap Dari Bisikan Novel : Feminist Perspective - Esamada Rose Nursaputri; Sulistyaningsih Sulistyaningsih (JournEEL, 2023)
Feminism is not a new theme in the world of literature. The purpose of this research is to describe the study of feminism in Andina Dwifatma's novel Lebih Senyap Dari Bisikan. A qualitative descriptive analysis of the Lebih Senyap Dari Bisikan novel was done. The novel's literary features were noted by the author and examined in this research. In this study, the authors of the new work reveal data in the words, phrases, and sentences they use. Feminist theory was used to analyze the issue. The results showed this novel contents three types of feminism. That are liberal feminism 55,55% (5 data of 9), radical feminism 22,22% (2 data of 9), and existentialist feminism 11,11% (1 datum of 9).